Development of Construct 2-based Educative Game in The Topic of Environmental Pollution - Nur Hasanah; Nur Qomaria; Badrud Tamam; Dwi Bagus Rendy Astid Putra; Aditya Rakhmawan (Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Jember, 2022)
This study aims to determine student responses and feasibility of construct 2-based educative game in the topic of environmental pollution. This study is included in the research and development using Waterfall development model. This model consists of five stages, namely analysis, design, implementation (coding), testing and maintenance. The test subjects in this study were 30 students of class VII B, MTs Sumenep. The results of the feasibility test of the construct 2-based educative game obtained an average validity value of 82.5% with a very valid category and an expert reliability value of 95.5% with a very reliable category. The results obtained from the student response questionnaire were 87.16% with very good criteria. Therefore, it can be concluded that construct 2-based educative game in environmental pollution topic can be used in the learning process.